Metabolite identification and pharmacokinetic profiling of PP242, an ATP-competitive inhibitor of mTOR using ultra high-performance liquid chromatography and mass spectrometry - Rashid, Md. Mamunur; Lee, Hyunbeom; Jung, Byung Hwa (ELSEVIER SCIENCE BV, 2018)
PP242 is a second generation novel selective ATP-competitive inhibitor of mTOR that displayed promising anticancer activity over several cancer types by inhibiting both the complexes of mTOR (mTORC1 and mTORC2). The purpose of this study is to identify the possible metabolites and to evaluate the pharmacokinetic profile of PP242 after a single oral administration to Sprague-Dawley (SD) rats. Two metabolites, including one phase I and one phase II, were identified by in vitro and in vivo studies using rat liver microsomes (RLMs) as well as rat plasma, urine and feces, respectively, through ultra high-performance liquid chromatography-linear ion trap quadrupole-orbitrap-mass spectrometry (UHPLC-LTQ-Orbitrap-MS). The major biotransformation pathways of PP242 were hydroxylation and glucuronide conjugation. Additionally, a simple and rapid quantification method was developed and validated. The method recovery was within 79.7-84.6%, whereas the matrix effect was 78.1-96.0% in all three quality control (QC) concentrations (low, medium and high) including the LLOQ. Other parameters showed acceptable results according to the US food and drug administration (FDA) guidelines for bioanalytical method validation. Afterwards, pharmacokinetic parameters were evaluated in rat plasma by successfully applying the validated method using liquid chromatography-tandem mass spectrometry (LC-MS/MS). After a single oral administration at a dose of 5 mg/kg, the maximum plasma concentration (C-max) of PP242 was 0.17 +/- 0.08 mu/mL, while the elimination was moderately fast (T-1/2: 172.18 +/- 45.54 min). All of the obtained information on the metabolite identification and pharmacokinetic parameter elucidation could facilitate the further development of PP242.
Keywords: CELL-PROLIFERATION; MAMMALIAN TARGET; RATS; PROGRESSION; CANCER